Identification of cell-surface glycans that mediate motility-dependent binding and internalization of Pseudomonas aeruginosa by phagocytes. (March 2021) - Sanchez, Hector; Hopkins, Daniel; Demirdjian, Sally; Gutierrez, Cecilia; O'Toole, George A.; Neelamegham, Sriram; Berwin, Brent
Highlights: We identify that N-linked glycans and glycosaminoglycans on phagocytes mediate binding and internalization of P. aeruginosa . The cell-surface glycans, by virtue of engaging P. aeruginosa, also mediate a variety of relevant host responses to P. aeruginosa, including inflammation and cytotoxicity. P. aeruginosa binding of immobilized heparin is dependent upon the flagellar motility of the bacteria. Abstract: Phagocytic cells are critical to host defense against Pseudomonas aeruginosa, a Gram-negative bacterium that is an opportunistic pathogen. Accordingly, susceptible individuals frequently have impaired innate immune responses, including those with cystic fibrosis or neutropenia. Previous studies identified that the downregulation, or loss, of bacterial flagellar motility enables bacteria to evade interactions with phagocytic cells that result in phagocytic uptake of the bacteria. However, the mechanistic bases for motility-dependent interactions between P. aeruginosa and host cell surfaces that lead to phagocytic uptake of the bacteria are poorly understood. A recent insight is that exogenous addition of a negatively charged phospholipid, phosphatidylinositol-(3, 4, 5)-triphosphate (PIP3 ), promotes the engagement of non-motile strains of P. aeruginosa with phagocytes leading to uptake of the bacteria. Thus, we hypothesized that the engagement of P. aeruginosa by phagocytic cells is mediated by motility-dependent interactions with cell-surface polyanions. Here we report that endogenous polyanionic N-linked glycans and heparan sulfate mediate bacterial binding of P. aeruginosa by human monocytic cells. These specific interactions resulted in P. aeruginosa phagocytosis, bacterial type 3 secretion system (T3SS)-mediated cellular intoxication and the IL-1β response of host innate immune cells. Importantly, the bacterial interactions with the glycans were motility-dependent and could be recapitulated with purified, immobilized glycans. Therefore, this work describes novel interactions of P. aeruginosa with specific phagocyte cell-surface glycans that modulate relevant host innate immune responses to the bacteria, including phagocytosis, inflammation and cytotoxicity.